Dangerous Premises: An Insider's View Of OSHA Enforcement - Parsons, Michael D. (Relations industrielles / Industrial Relations, 1991)
The article reviews the book, "Dangerous Premises: An Insider's View Of OSHA Enforcement," by Don J. Lofgren.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Laws & regulations; Occupational health & safety; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z